Design of Adaptive Filter for Laser Gyro - Xiao Jun Yan; Jin Ming Li; Ze Ming Li; Yan Jiao Yang; Cheng Rui Zhai (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
According to the filtering of laser gyro output signal of low precision, slow speed of dynamic response, the research and implementation of a new method of laser gyro filtering process, the scheme using LMS adaptive filtering algorithm, the dither feedback signal as the iterative filter data input, the dither signal, random noise, white noise as the reference signal filter, digital filter and the external control using FPGA, give the filter algorithm and hardware block diagram. Experimental results show that the filtering module with filter with high precision and wide dynamic response range, can meet the requirements of speed and precision of laser gyro demodulation aerospace fields.